2010
DOI: 10.1088/0741-3335/52/10/105011
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the JET current ramp-up experiments and projection to ITER

Abstract: The current ramp up phase of ITER demonstration discharges, performed at JET, is analysed and the capability of the empirical L-mode Bohm-gyroBohm and CoppiTang transport models as well as the theory-based GLF23 model to predict the temperature evolution in these discharges is examined. The analysed database includes ohmic (OH) plasmas with various current ramp rates and plasma densities and the L-mode plasmas with the ion cyclotron radio frequency (ICRF) and neutral beam injection (NBI) heating performed at v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…Also in AUG the neoclassical calculation yielded a too fast current penetration during the ohmic ramp-up phase [5]. On the other hand, the calculated current diffusion in the later part of the ramp-up in JET can be matched with the observations, by adjusting the profiles of Z eff and T e within the experimental uncertainties [6]. Moreover, the observed relaxation of the q profile after the L-H transition in JET is reported to be in agreement with neoclassical calculations [7].…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Also in AUG the neoclassical calculation yielded a too fast current penetration during the ohmic ramp-up phase [5]. On the other hand, the calculated current diffusion in the later part of the ramp-up in JET can be matched with the observations, by adjusting the profiles of Z eff and T e within the experimental uncertainties [6]. Moreover, the observed relaxation of the q profile after the L-H transition in JET is reported to be in agreement with neoclassical calculations [7].…”
Section: Introductionmentioning
confidence: 73%
“…Validation on the ramp-up phase of JET, AUG and Tore Supra [6,8,9] has shown that both empirical scaling based models and the semi-empirical Bohm/gyro-Bohm model (L-mode version, ITB shear function off, [10]) yield a good reproduction of this phase for considered discharges, in terms of T e profile and l i . Therefore these two models have been used in the reported work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently become clear that stringent constraints are put on the operational scenario of the ITER current rampup (CRU) and current ramp-down (CRD) phases, for several reasons discussed in the literature ( [1] and references therein). In this respect, most of the focus now in the ITER modelling activity, see for example [2][3][4][5][6][7][8][9], is on predicting how the relevant plasma parameters will evolve during the current ramp-up and ramp-down phases, allowing optimization studies before the machine is built and operated.…”
Section: Introductionmentioning
confidence: 99%
“…These parameters exhibit strong nonlinear dependencies. Recent experiments on DIII-D [2,3] and other tokamaks [4,5] have sought to simulate an ITER-like ramp-up in order to test these models, as well as to optimize the ramp-up scenario [6].…”
Section: Introductionmentioning
confidence: 99%